Analisis Permasalahan Dalam Pembelajaran IPA Sekolah Dasar Swasta Attaufiq Medan - Maya Fadillah; Fika Luh Cinta; Ruth Sani Friscilla Purba; Annisa Fitriana Batubara; Andini Andriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to find out the problems found in science learning at SDS AT-TAUFIQ Medan. The method used in this research is a qualitative method with a descriptive approach. Data was obtained through interviews. The results of this research show that there are still many problems related to science learning at Attaufiq Medan Private Elementary School. The basic problem is the lack of motivation and enthusiasm of students in the learning process. The lack of facilities and infrastructure is also a problem in science learning at SDS At-Taufiq Medan. By making innovations such as applying learning media, you can create a comfortable and enjoyable learning atmosphere.